Understanding media influence on parental perspectives towards child obesity prevention - Wang, Qian; Normaliza Abd. Rahim,; Nurzihan Hassim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The advocacy for children’s health and wellness through multiple media platforms is pertinent in raising awareness among parents as the World Health Organization (WHO) identified child obesity as one of the most serious public health challenges of the 21st century. Malaysia is currently ranked with the highest obesity population in Southeast Asia, a clear indication that intervention campaigns implemented to improve the obesity conundrum in the past have met with little success. Although studies have shown that parents exercise considerable influence on nutrition and eating habits of children, their information-seeking habits in their position as decision makers of the household remains a significant oversight. Therefore, effective health communication strategies in the media targeted towards this segment highlight the importance of child obesity prevention information, particularly among low-income groups in urban communities. This study examined media and communication strategies on child obesity by exploring how parents negotiate information to ensure children abide by healthier practices. In doing so, a diary study was conducted to observe behaviours of the target group in dealing with information on child obesity on a daily basis. The result of the study is congruent with the assumption that parents have great potential to organically formulate child obesity prevention plans with their extent of exposure towards media messages. Henceforth, the role of media is seen as a highpoint in creating awareness on health communication strategies that can further engage and assist Malaysian parents for a more sustainable future for their children.